Exports, foreign direct investment and economic growth: Empirical evidence from Malaysia (1971-2013) - Haseeb, Muhammad; Hartani, Nira Hariyatie; Abu Bakar, Nor'Aznin; Azam, Muhammad; Hassan, Sallahuddin (Science Publications, 2014)
The main objective of this study is to empirically investigate the relationship between exports, Foreign Direct Investment (FDI) and the economic growth in Malaysia.Records of annual time series data from the year 1971 till 2013 have been utilized for this purpose. Upon testing the data for stationarity, the Auto Regressive Distributed Lag (ARDL) model has been applied for the purpose of empirical investigation.The empirical results indicate that the productivity factor and externality effect of exports on the non-export sector are found to be statistically, positively significant, with the exports also having a positive impact on the economic growth and FDI of the country.The results support Exports Led Growth (ELG) and FDI-Led economic Growth (FLG) in Malaysia. The finding further suggests that Malaysia should continuous pursue exports promotion and a liberal investment economic policy in order to maintain and bolster overall economic growth.